A Comparative Study of Milk Producer Companies Vis-A-Vis Traditional Milk Cooperatives in Saurashtra Region of Gujarat - Singh, Ritambhara; Pundir, R. S. (Indian Journal of Marketing, 2016)
In a sector like dairy, that too in Gujarat, where a dairy cooperative giant, Gujarat Cooperative Milk Marketing Federation exists, the presence of the very first milk Producer Company, that is, Maahi Milk Producer Company Limited, has not gone unnoticed. This case study attempted to find if a milk producer company can be an alternative to traditional milk cooperatives or if both of them can coexist? The study focused on exploring the structural and operative differences between two institutions, assessing their profitability, and identifying the constraints facing their development. The study will be useful to the management of both institutions. The study revealed that milk producer companies could be an available alternative to milk cooperatives. However, the presence of both in the study area brought more milk to the organized sector, reducing the exploitation of milk producers by private dairies and milk vendors in terms of prices, milk weighing, and timely payment. There is a win-win situation for the farmers, which can further be strengthened by strong coordination between two institutions. However, it seems quite difficult as both organizations operate in the same region, and therefore, business competition cannot be ruled out. The milk producer company, unlike a cooperative, makes payment through a bank account, which has created a strong perception of its transparent operations in the minds of milk producers. The same needs to be practiced by dairy cooperatives too. It was observed that traditional milk cooperatives paid slightly higher procurement price, but appeared not to attract milk producers.